A delayed diagnosis of catecholaminergic polymorphic ventricular tachycardia with a mutant of RYR2 at c.7580T>G for 6 years in a 9-year-old child. Issue 16 (April 2018) - Duan, Hongyu; Lu, Yongyi; Yan, Song; Qiao, Lina; Hua, Yimin; Li, Yifei; Zhou, Kaiyu; Wang, Chuan
Abstract: Rationale: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare but potentially lethal inherited arrhythmia syndrome induced by adrenergic stress. Due to the atypical clinical manifestations in early age, limited recognition and experience of pediatric cardiologists, and low awareness of the significance of genetic diagnosis in some underdeveloped areas in China, a delayed or missed diagnosis of CPVT in children is common and concerning. Patient concerns: A 9-year and 3-month male child with recurrent exercise-induced syncope accompanied by convulsion was initially misdiagnosed as epilepsy since the first manifestation at the age of 3 years. Due to the identification of polymorphic ventricular premature beats, nonsustained ventricular tachycardia (VT), and supraventricular tachycardia, a cardiogenic etiology was established. The patient received a successive treatment by propafenone, amiodarone, a combination of amiodarone with metoprolol, and metoprolol alone for up to 6 years. Diagnoses: Given the poor response to conventional antiarrhythmics, excise-induced syncope, QRS morphology and a structurally normal heart, the diagnosis of CPVT was suspected, and ultimately confirmed by detection of polymorphic and bidirectional VT with degeneration into ventricular fibrillation during exercise testing. In addition, a heterozygous mutant of RYR2 at c.7580T > G was identified by genetic testing. Interventions: Due to the unavailability of flecainide in China and the refusal of implantable cardioverter defibrillator implantation by his parents, this patient continued to be treated with oral metoprolol. Outcomes: Unfortunately, the effect was unfavorable during 4 months outpatient follow-up. Lessons: CPVT should be suspected in young patients with a normal baseline electrocardiogram (EKG), a structurally normal heart and polymorphic and/or bidirectional ventricular tachycardia induced by exercise or emotional stress. Exercise and genetic testing is essential and significant for a timely and accurate diagnosis of CPVT. The current study firstly reported a case with CPVT associated with a mutant of RYR2 at c.7580T > G in children.